Evaluation of antihyperglycemic activity of plants in northeast mexico - Adame-Miranda, Sara J.; Granados-Guzmán, Graciela; Silva-Mares, David A.; Acevedo-Fernández, Juan José; Waksman-Minsky, Noemí; Salazar-Aranda, Ricardo (Cellular and Molecular Biology, 2021)
iabetes mellitus is one of the most common non-contagious diseases. In 2017, The International Diabetes Federation reported that around 425 million people suffer from diabetes worldwide. Medications used for the treatment of diabetes lead to unwanted side effects, and thus, new safe drugs are necessary. Some natural plant-based products exhibit anti hyperglycemic activity and low toxicity. The aim of this study was to evaluate the antihyperglycemic activity (using both in vitro and in vivo models) as well as cytotoxicity of the extracts obtained from various plants. Nine extracts from a total of eight plant species were subjected to in vitro Î±-amylase and Î±-glucosidase inhibition assays. Subsequently, they were assessed through the ex vivo everted sac assay, and finally, the in vivo antihyperglycemic activity was evaluated. The extracts obtained from Ceanothus coeruleus, Chrysactinia mexicana and Zanthoxylum fagara inhibited the activities of Î±-amylase and Î±-glucosidase in the in vitro assays. Ethyl acetate and hydroalcoholic extracts from Jatropha dioica, hydroalcoholic extract from Salvia ballotaeflora and Chrysactinia mexicana, as well as methanolic extract from Ricinus communis and Zanthoxylum fagara significantly reduced the glucose uptake in the ex vivo everted intestinal sac test. All the eight extracts showed antihyperglycemic effect through the in vivo model of the Glucose Tolerance Test, using starch as the carbohydrate source.  The antihyperglycemic effect of the extracts could be mediated through the inhibition of digestive enzymes and/or the absorption of glucose through the intestine. However, the mechanism of action for the hydroalcoholic extract of Salvia texana and the methanolic extract of Turnera diffusa, which showed a strong in vivo antihyperglycemic effect, is unclear.